Evaluating the commercialization of smallholder malt barley farmers via vertical coordination in Arsi highlands, Oromia region, Ethiopia - Addisu Bezabeh; Fekadu Beyene; Jema Haji; Tesfaye Lemma (Cogent Economics & Finance, 2022)
Smallholder farmers search for their product buyers in local spot market transactions. In spot market transactions, farmers will not be assured of ready markets for their production, or face volatile market prices. Similarly malt barley farmers used to face challenges of accessing input, farm technology, credit, and information that undermine their livelihoods. Vertically coordinated malt barley supply chain is evolving fast in Ethiopia. The purpose of this study was to analyze nexus between vertical coordination and level of malt barley commercialization in the study area. This study has been conducted in four districts of Arsi highlands known for their malt barley production potentials and presence of active supply chain coordination. A three-stage sampling procedure was employed to collect data using interview schedule from 384 (190 contract and 194 non-contract) randomly selected malt barley farmers. Descriptive statistics and Tobit regression model used to analyze farmer and farm-related factors vis-à-vis vertical coordination and level and determinants of commercialization farm households. Accordingly, the study identified that 11.05% of the respondents had <30% level of commercialization, when 55% were in between 30% and 65% and the rest, 34.21% of sampled malt barley farm households had more than 65% level of malt barley commercialization. Tobit regression revealed that farm size, yield, price, quantity of fertilizer applied, contract agreements, mobile phone ownership and access to credit were determinants of level of malt barley commercialization. Thus, endeavors of malt barley commercialization have to focus on improving access to technology, credit, extension, and organizing farmers in contract farming among others.
Keywords: 330; Arsi zones; Commercialization; malt barley; smallholder; Tobit